A Rechargeable Al/S Battery with an Ionic‐Liquid Electrolyte. (15th July 2016) - Gao, Tao; Li, Xiaogang; Wang, Xiwen; Hu, Junkai; Han, Fudong; Fan, Xiulin; Suo, Liumin; Pearse, Alex J; Lee, Sang Bok; Rubloff, Gary W.; Gaskell, Karen J; Noked, Malachi; et al.
Abstract: Aluminum metal is a promising anode material for next generation rechargeable batteries owing to its abundance, potentially dendrite‐free deposition, and high capacity. The rechargeable aluminum/sulfur (Al/S) battery is of great interest owing to its high energy density (1340 Wh kg −1 ) and low cost. However, Al/S chemistry suffers poor reversibility owing to the difficulty of oxidizing AlS x . Herein, we demonstrate the first reversible Al/S battery in ionic‐liquid electrolyte with an activated carbon cloth/sulfur composite cathode. Electrochemical, spectroscopic, and microscopic results suggest that sulfur undergoes a solid‐state conversion reaction in the electrolyte. Kinetics analysis identifies that the slow solid‐state sulfur conversion reaction causes large voltage hysteresis and limits the energy efficiency of the system.